Changes in nerve growth factor signaling in female mice with cyclophosphamide-induced cystitis - Hsiang, Harrison W.; Girard, Beatrice M.; Vizzard, Margaret A. (Frontiers in Urology, 2023)
IC/BPS is a chronic inflammatory pelvic pain syndrome characterized by lower urinary tract symptoms including unpleasant sensation (pain, pressure, or discomfort) in the suprapubic or bladder area, as well as increased urinary frequency and urgency, and decreased bladder capacity. While its etiology remains unknown, increasing evidence suggests a role for changes in nerve growth factor (NGF) signaling. However, NGF signaling is complex and highly context dependent. NGF activates two receptors, TrkA and p75NTR, which activate distinct but overlapping signaling cascades. Dependent on their coexpression, p75NTR facilitates TrkA actions. Here, we show effects of CYP treatment and pharmacological inhibition of p75NTR (via LM11A-31) and TrkA (ARRY-954) on NGF signaling–related proteins: NGF, TrkA, phosphorylated (p)-TrkA, p75NTR, p-ERK1/2, and p-JNK. Cystitis conditions were associated with increased urothelial NGF expression and decreased TrkA and p75NTR expression as well as altering their co-expression ratio; phosphorylation of ERK1/2 and JNK were also altered. Both TrkA and p75NTR inhibition affected the activation of signaling pathways downstream of TrkA, supporting the hypothesis that NGF actions during cystitis are primarily TrkA-mediated. Our findings, in tandem with our recent companion paper demonstrating the effects of TrkA, TrkB, and p75NTR inhibition on bladder function in a mouse model of cystitis, highlight a variety of potent therapeutic targets and provide further insight into the involvement of NGF signaling in sustained conditions of bladder inflammation.